KONSEPSI HAK MASYARAKAT HUKUM ADAT SEBAGAI HAK ASASI MANUSIA DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Zein, Yahya Ahmad; Nurvianti, Dewi (Veritas et Justitia, 2017)
This article discusses the "conception of adat law community rights as a human right. The purpose of writing this article is to know the conception of customary law community as a human right, with limited review of legislation relating to the topic.This article is important to publish, considering many issues that arise related to the rights of adat law community. Starting from the use of the term to the fulfillment of the rights of adat law community. As known that until now there has been no legislation that specifically regulates the rights of adat law community. In the highest regulation under Article 18 B paragraph 2 and Article 28 I paragraph 3 of the 1945 Constitution, the rights of adat law community are further regulated in several laws and regulations, so that it will be difficult to identify what rights should be met by countries for the fulfillment of the rights of adat law community.This article discusses some statutory legislation in Indonesia which is the foundation for accommodating customary law community rights which are human rights where the fulfillment must be done by the state.